Evaluation of Double-Faced Tubularized Preputial Flap versus Duckett's Procedure for Repair of Penoscrotal Hypospadias with Significant Penile Curvature: A Comparative Study. (21st September 2022) - Shahin, Mohamed; Abdalrazek, Mohamed; Abdelmaboud, Mohamed; Elsayaad, Ibrahim Mahmoud; Mahmoud, Muhammad Abdelhafez; Mousa, Mahmoud Abdelhady; Elshamy, Ahmed; Alsamahy, Omar; Rehan, Mohamed; Elhady, Sayed; Gamaan, Ibrahim
Abstract : Background . Proximal hypospadias, with significant curvature, is one of the most challenging anomalies. Great diversity and a large number of procedures described over the last 4 decades confirmed the fact that no single procedure has been universally accepted or successful. So, the aim of this study is to evaluate double-faced tubularized preputial flap (DFPF) versus transverse tubularized inner preputial flap (Duckett's procedure) as regards surgical outcomes, complications rate, and cosmetic results for repair of penoscrotal hypospadias with chordee. Patients and Methods . This was a prospective comparative study on 144 children with primary penoscrotal hypospadias with moderate or severe chordee, conducted at New Damietta and Assuit hospitals, Al-Azhar University, from March 2016 to March 2022. The patients were randomly divided into two equal groups; group A ( n = 72) underwent DFPF, and group B ( n = 72) underwent Duckett's procedure. Results . No significant difference was identified as regards demographic data. The follow-up period ranged from 20 to 66 months (mean of 28 months after DFPF and 31 months after Duckett's repair), and the complication rate was 20.1% (29 of 144 children). There were statistically significant differences between the two groups as regards the urethral stricture, penile rotation, and total complication rate. HOSE score was adopted for assessment of surgical outcomes, urine stream, and cosmetic results. Conclusions . The DFPF technique is feasible and reliable for one-stage repair of penoscrotal hypospadias with chordee and can be considered as a good option as it ensures better surgical and cosmetic outcomes with lower incidence of complications.